2014
DOI: 10.4238/2014.january.10.11
|View full text |Cite
|
Sign up to set email alerts
|

Application of genomics and proteomics in drug target discovery

Abstract: ABSTRACT. Gene medicine is making breakthroughs in health questions that have baffled humanity for centuries. To understand and utilize gene medicine, it is necessary to realize its action against targets at the molecular level. Currently, many methods can be used to discover drug targets; among these, genomic and proteomic methods are the two most important. In this study, we introduced how to discover drug targets by genomic and proteomic methods in detail. These contents are beneficial for understanding and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Data obtained from genome analysis and transcription studies of specific genes are not sufficient to ensure high active protein yield. The expression "one gene, one protein" is not accurate, as it has been confirmed that the average number of protein isoforms per gene is one or two in bacteria, three in yeast, and three or more in humans because of the formation of protein isoforms produced by different forms of posttranslational modifications (phosphorylation, glycosylation, nitrosation, ethylation, and methylation) [20]. Bioinformatics analysis may reveal potential posttranslational modifications in certain proteins.…”
Section: Drug Design and Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Data obtained from genome analysis and transcription studies of specific genes are not sufficient to ensure high active protein yield. The expression "one gene, one protein" is not accurate, as it has been confirmed that the average number of protein isoforms per gene is one or two in bacteria, three in yeast, and three or more in humans because of the formation of protein isoforms produced by different forms of posttranslational modifications (phosphorylation, glycosylation, nitrosation, ethylation, and methylation) [20]. Bioinformatics analysis may reveal potential posttranslational modifications in certain proteins.…”
Section: Drug Design and Discoverymentioning
confidence: 99%
“…Proteomics studies have broadened the perspective of protein research to examine the consequences of protein function in establishing the phenotype and interaction of a drug with its target. These studies have also revealed the pathophysiological basis of disease, validation of drug targets, action, toxicity, and side effects [20].…”
Section: Drug Design and Discoverymentioning
confidence: 99%
“…Além disso, uma investigação das principais vias bioquímicas possibilita a identificação de proteínas essenciais para o crescimento e desenvolvimento do micro-organismo alvo. Já uma análise comparativa dos organismos pode levar, preferencialmente, à seleção de proteínas ausentes no hospedeiro ou então com importantes diferenças estruturais em relação às proteínas que desempenham função análoga em humanos, culminando em ligantes seletivos e minimizando problemas como inespecificidade e toxicidade (Zhang et al 2014) Esta revisão concentrará nas abordagens quimioproteômicas utilizadas para a descoberta de alvos de fármacos e rastreamento de compostos com potencial terapêutico, como cromatografia de afinidade, perfil de proteínas baseado na atividade e estabilidade, imobilização de moléculas usando microarranjo de proteínas e rastreio virtual.…”
Section: Introductionunclassified
“…Literature survey reveals that several analytical methods have been reported for the determination of miconazole nitrate (MIC) alone or in combinations including spectrophotometry [3][4][5][6][7][8][9][10][11], spectrofluorometry [4] and HPLC [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Besides, several analytical methods have been reported for the determination of hydrocortisone acetate (HYD) alone or in combination with other drugs including spectrophotometry [31][32][33][34][35], and HPLC [36][37][38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%